The Effectiveness of the Accelerated Learning Model Assisted by Audiovisual Media on the History Learning Outcomes of Students at SMA Negeri 2 Ponorogo - Dian Nur Antika Eky Hastuti (Riwayat: Educational Journal of History and Humanities, 2024)
This research is motivated by the fact that history education still employs lecture methods, causing students to be passive in learning history, which in turn affects their history learning outcomes negatively. The aim of this research is to determine the effectiveness of the Accelerated Learning model assisted by audiovisual media on the history learning outcomes of students at SMA Negeri 2 Ponorogo. The method used in this research is quantitative research with a True Experimental Design, specifically a Posttest Only Control Design. The population in this study consists of all 148 tenth-grade students at SMA Negeri 2 Ponorogo, and the sampling technique used is Simple Random Sampling, with class X.A as the experimental class and class X.C as the control class. Data collection was conducted through learning outcome tests or posttests with multiple-choice variants. Data analysis utilized the t-test statistical method, with normality and homogeneity tests conducted on the posttest data as prerequisites. The research showed that the calculated t-value (9.37) is greater than the table t-value (1.686), leading to the rejection of H0 and acceptance of H1, thus indicating an influence on student learning achievement. The observation sheet of student activity results scored 82, indicating good interaction between teachers and students with the Accelerated Learning model. This means that learning using the Accelerated Learning model assisted by audiovisual media is more effective than the Accelerated Learning model without audiovisual media in improving the history learning outcomes of students at SMA Negeri 2 Ponorogo.